Effect of Ligilactobacillus salivarius and Other Natural Components against Anaerobic Periodontal Bacteria - Marzena Kucia; Ewa Wietrak; Mateusz Szymczak; Paweł Kowalczyk (Molecules, 2020)
In this present study, the bacteriostatic effect of Salistat SGL03 and the Lactobacillus salivarius strain contained in it was investigated in adults in in vivo and in vitro tests on selected red complex bacteria living in the subgingival plaque, inducing a disease called periodontitis, i.e., chronic periodontitis. Untreated periodontitis can lead to the destruction of the gums, root cementum, periodontium, and alveolar bone. Anaerobic bacteria, called periopathogens or periodontopathogens, play a key role in the etiopathogenesis of periodontitis. The most important periopathogens of the oral microbiota are: Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola and others. Our hypothesis was verified by taking swabs of scrapings from the surface of the teeth of female hygienists (volunteers) on full and selective growth media for L. salivarius. The sizes of the zones of growth inhibition of periopathogens on the media were measured before (in vitro) and after consumption (in vivo) of Salistat SGL03, based on the disk diffusion method, which is one of the methods of testing antibiotic resistance and drug susceptibility of pathogenic microorganisms. Additionally, each of the periopathogens analyzed by the reduction inoculation method, was treated with L. salivarius contained in the SGL03 preparation and incubated together in Petri dishes. The bacteriostatic activity of SGL03 preparation in selected periopathogens was also analyzed using the minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC) tests. The obtained results suggest the possibility of using the Salistat SGL03 dietary supplement in the prophylaxis and support of the treatment of periodontitis—already treated as a civilization disease.